In vitro immunogenic and immunostimulatory effects of zwitterionized 23-valent pneumococcal polysaccharide vaccine compared with nonzwitterionized vaccine. - Abdulamir, Ahmed Sahib; Hafidh, Rand Riadh; Abu Bakar, Fatimah (Elsevier, 2010)
Background: It was hypothesized that the observed slight immunostimulatory effect of the 23-valent pneumococcal polysaccharide (pneumo-23) vaccine might be due to the presence of low levels of zwitterionic motifs. Therefore, it was hypothesized further that introducing zwitterionic motifs experimentally into polysaccharides of pneumo-23 vaccine might render it an effective immunostimulatory agent.